2020
DOI: 10.1111/jace.17495
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of La0.7Sr0.3MnO3 under the pressure and the transport property under the magnetic field

Abstract: Polycrystalline La 0.7 Sr 0.3 MnO 3 sample (LSMO) was synthesized by the solid phase reaction; it exhibits the paramagnetic-ferromagnetic transition at T c = 362 K at the ambient pressure; it is paramagnetic metallic state above T c and the ferromagnetic metallic state below T c. It was observed that the pressure effect depends on the temperature range: (a) In the paramagnetic region, the magnetization M hardly changes with the pressure P, that is, ΔM≈0. There exist the antiferromagnetic (AFM) coupled ferromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…83 Such lattice changes would be in favor of the DE and multiple DE interactions and, consequently, promote the magnetic ordering transition to higher temperatures, as shown recently for similar manganite compounds. 87…”
Section: Magnetic Properties Of the Lmo-1150 Ceramics At High Pressuresmentioning
confidence: 99%
“…83 Such lattice changes would be in favor of the DE and multiple DE interactions and, consequently, promote the magnetic ordering transition to higher temperatures, as shown recently for similar manganite compounds. 87…”
Section: Magnetic Properties Of the Lmo-1150 Ceramics At High Pressuresmentioning
confidence: 99%
“…In addition, Eu 3+ has a small ionic radius and its 4 f orbital is half-full and full-full, so the bulk manganese oxide Eu 0.7 Sr 0.3 MnO 3 (ESMO) exhibits the boundary properties of ferromagnetism (FM) and antiferromagnetism (AFM) [11,12], but the magnetic and electronic behavior of epitaxial ESMO thin films have been little studied. Moreover, the lattice distortion due to the strain effect is manifested in MnO 6 octahedral distortion and rotation [13], which is closely related to the e g electron bandwidths of Mn ions [14][15][16], so the influence on magnetic properties and electronic phases are more obvious in narrow-bandwidth ESMO films, especially under external stimuli such as magnetic field, electric field, pressure, and light [17][18][19]. Moon et al [12] reported that Eu 0.7 Sr 0.3 MnO 3 thin films grown on substrates with relatively matched lattices exhibit ferromagnetic and insulating properties.…”
Section: Introductionmentioning
confidence: 99%